Karakterisasi Molekuler Ikan Gurami Soang (Osphronemus gouramy Lac.) yang Mati pada Rentang Waktu Berbeda Menggunakan PCR-RFLP Gen Major Histocompatibility Complex Kelas II B - Jaka Tri Spetiawan; Agus Nuryanto; Hendro Pramono; Kusbiyanto Kusbiyanto; Petrus H. Tjahja Soedibja (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2016)
Gurami (Osphronemus gouramy Lac.) is a popular fish species among Indonesian people. Several Gurami strains have been cultivated by fish farmer, one of which is Gurami Soang. This strain is belived to have a faster growth rate compared to other strains. However, like other strains, the fingerling of Soang strain have also a low survival and suceptible to disease, especially that caused by Aeromonas hydrophila infection. It has been proved that seeds from a single spawning event show varibale disease resistance. The difference in resistance among individuals is suggested related to the difference in their genetic component. One of the genes responsible for resistance is Major Histocompatibility Complex (MHC) class II B gene. Variability in resistance can be analyzed by using PCR - RFLP technique. PCR-RFLP is a technique that can produce a specific DNA fragments by PCR, followed by cutting the PCR product using restriction enzymes to describe the presence or absence of restriction sites in DNA fragments. This research aims to determine genetic marker to differiantiate between resitant and irresistant individual of Gurami Soang infected by A. hydrophila which die at a different time priod based on PCR-RFLP MHC class IIB gene. The study used survey method with purposive random sampling. The Data of PCR-RFLP band patterns were analyzed descriptively. The result indicated that cutting of the MHC class II B gene using HinfI produce two RFLP bands with 300 bp and 100 bp length in all samples. Meanwhile, the MHC IIB gene was not cuted by PstI, HindIII, BamHI and EcoRI enzymes forall samples. These mean that MHC II gene in all individuals were monomorphic. Therefore,it can be concluded that there is no specific genetic marker to differentiate gurami soang individulas which was dying in different time periods.